2019
DOI: 10.1097/cm9.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenovirus-mediated overexpression of PTEN on brain oxidative damage and neuroinflammation in a rat kindling model of epilepsy

Abstract: Background:Epilepsy is a chronic and severe neurological disorder. Phosphatase and tensin homolog deleted on chromosome ten (PTEN)-deficient mice exhibit learning and memory deficits and spontaneous epilepsy. The aim of this study was to investigate the role of PTEN in brain oxidative damage and neuroinflammation in a rat model of epilepsy.Methods:An adenovirus (Ad)-PTEN vector was constructed, and status epilepticus (SE) was induced in 41 model rats using lithium chloride-pilocarpine. Thirty-six SE rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…All these changes could increase the neuronal network excitability and diminish cell survival and seizure threshold. These data correspond to clinical and experimental studies in which there have been increased levels of IL-1β and TNF-α demonstrated in patients with temporal lobe epilepsy and humans exposed to SE [4,12], as well as in animals with SE [13].…”
Section: Introductionsupporting
confidence: 88%
“…All these changes could increase the neuronal network excitability and diminish cell survival and seizure threshold. These data correspond to clinical and experimental studies in which there have been increased levels of IL-1β and TNF-α demonstrated in patients with temporal lobe epilepsy and humans exposed to SE [4,12], as well as in animals with SE [13].…”
Section: Introductionsupporting
confidence: 88%
“…Besides its immune modulatory and pro‐inflammatory potential, HMGB1 interacts with TLR4 on neutrophils to induce oxidative stress 6 . The HMGB1 induced oxidative stress results in a progressive neuronal damage 7,8 . The HMGB1‐mediated activation of TLR4/RAGE pathway is one of the contributing factors to epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate genes were selected with the goal of capturing several proposed mechanisms underlying postoperative seizure pathophysiology from prior literature. To conserve statistical power in this pilot study, we selected a total of 10 genes across genes that were either previously studied in the setting of surgical epilepsy seizure outcomes (DEPDC5, NBEA, SCN1A) (6), or studied as potential mechanisms for the cause or maintenance of the epileptogenic zone in focal epilepsy (6,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). These mechanisms included: neuroinflammatory causes of epileptogenesis (IL1A, C3) (17), calcium regulation and its role in induction and maintenance of epilepsy (CALHM1) (17, 21), mTOR pathway regulation in focal epileptogenesis (DEPDC5, PTEN) (6,15,18,20,22), monogenic causes of focal epilepsy (SCN1A, GABBRA1, LGI1) (16,17,23), established genetic causes of epileptic encephalopathies (NBEA) (6,18), and pharmaco-resistance mediating maintenance of seizures (ABCB1) (14,23,24).…”
Section: Genetic Variant Selection and Analysesmentioning
confidence: 99%